1991
DOI: 10.1620/tjem.164.309
|View full text |Cite
|
Sign up to set email alerts
|

The Stimulatory Effect of PACAP 38 on Amylase Release in Dispersed Rat Pancreatic Acini.

Abstract: Pituitary adenylate cyclase activating polypeptide 38 (PACAP 38), a novel peptide of the vasoactive intestinal polypeptide (VIP) family, was shown to stimulate enzyme secretion in the dispersed rat pancreatic acini. The dose-response of pancreatic enzyme secretion to PACAP 38 was nearly identical with that to VIP. In the presence of a submaximal dose of PACAP 38 (1 nM), amylase release stimulated by an agonist working via the elevation of intracellular cyclic AMP (VIP, dibutyryl CAMP) was additionally responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…We therefore concluded that PACAP27 stimulates pancreatic amylase secretion chiefly via intracellular CAMP. This conclusion is in agreement with our previous results (Kashimura et al 1991(Kashimura et al , 1992) and the observation by Raufman et al (1991) that PACAP38 stimulates pancreatic enzyme secretion via cAMP production.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…We therefore concluded that PACAP27 stimulates pancreatic amylase secretion chiefly via intracellular CAMP. This conclusion is in agreement with our previous results (Kashimura et al 1991(Kashimura et al , 1992) and the observation by Raufman et al (1991) that PACAP38 stimulates pancreatic enzyme secretion via cAMP production.…”
Section: Discussionsupporting
confidence: 94%
“…However, the secretagogues working via intracellular cAMP, including VIP, stimulate the amylase release at a constant rate (Peikin et al 1978;Pandol et al 1983Pandol et al , 1985. The initial burst of PACAP-stimulated amylase secretion demonstrated by our present and former (Kashimura et al 1992) studies indicate that PACAP stimulates exocrine pancreas partly via mechanisms other than the elevation of intracellular cAMP.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In guinea pig pancreatic acini, PACAP-38 alone has a dose-dependent stimulating effect on amylase secretion, with significant stimulation from 1 nM; on top of that, PACAP-38 also shifted CCK dose-response curve to the left by one order of magnitude (28). In rat pancreatic acini, PACAP-38 and VIP alone each stimulated amylase secretion; both enhanced CCKinduced amylase secretion without any shift in maximal CCKstimulating concentration (27).…”
Section: ϫ12mentioning
confidence: 89%